Mercado y consumo: economía política de las telecomunicaciones en Colombia (2013)
Based on financial statements reported by the main media and radio companies in Colombia, this article demonstrates supply and property concentration, as well as the existence of a hierarchy of sectors involved, according to their economic relevance. Additionally, based on a general media study –EGM– of the second semester of 2010, the article assesses the political importance of each sector in telecommunications: this is, infrastructure, radio diffusion and their contribution to the public sphere.